China's fish maw demand and its implications for fisheries in source countries. (October 2021) - Ben-Hasan, Abdulrahman; Sadovy de Mitcheson, Yvonne; Cisneros-Mata, Miguel A.; Jimenez, Érica Antunes; Daliri, Moslem; Cisneros-Montemayor, Andrés M.; Nair, Rekha J.; Thankappan, Sangeetha A.; Walters, Carl J.; Christensen, Villy
Abstract: The demand for fish maw (i.e., dried swim bladder) has apparently intensified during the past decades in Hong Kong and mainland China; currently, maw has similar annual import volumes but far higher mean unit values than other important seafood delicacies like shark fins and sea cucumber. Escalated demand for seafood delicacies can significantly contribute to the depletion of marine resources; yet a comprehensive understanding of maw value and the fisheries that supply it is lacking. We review available information on eight important maw-supplying species in major and largely undocumented source countries to examine the susceptibility and exposure of fisheries to the maw trade, which primarily serves Chinese demand. Comparing ex-vessel price ratios of maw to flesh (USD/kg), the overall mean price of maw can be as much as 72 times higher (range between 12:1 and 8389:1). Catch, price and export trends demonstrate that demand for maw is likely intensifying in countries already supplying it, shifting or expanding to new species, and emerging in new regions. We find that most maw-supplying species are under high fishing pressure, poorly or not protected. Those that yield the highest maw prices exhibit spawning aggregations, making them exceptionally vulnerable to overexploitation. While management interventions are needed to sustain fishery resources and capture economic benefits, their effectiveness will be challenged by the high value of maw.